Reduced nicotine dependence following traumatic brain injury in an elderly patient: a case report and literature review - Yuan, Min; Xu, Renshi (Frontiers in Human Neuroscience, 2025)
Traumatic brain injury (TBI) can induce a range of neurological and behavioral changes, including potential effects on substance dependence. We present the case of an 87-year-old male with a longstanding history of heavy smoking (~60 pack-years) who demonstrated an abrupt cessation of nicotine craving following a severe TBI involving subdural hemorrhage, contusions, and subarachnoid hemorrhage. Clinical management included supportive therapy for intracranial pressure control and infection management. Nicotine dependence and craving were qualitatively assessed through repeated structured clinical interviews during hospitalization and outpatient follow-up. Remarkably, during the six-month follow-up, the patient remained abstinent without signs of withdrawal or nicotine craving and the use of pharmacological or behavioral interventions. This case highlights a rare but significant phenomenon suggesting that severe brain injury may disrupt mesolimbic dopaminergic circuits, including the ventral tegmental area (VTA) and nucleus accumbens (NAc), central to nicotine-related reward processing. We discuss potential neurobiological mechanisms post-injury, including dopaminergic dysfunction and health behavior adaptation. Further research is needed to elucidate the underlying pathways and clinical implications of TBI-associated changes in addictive behaviors.